Research progress of nanomaterials in tumor-targeted drug delivery and imaging therapy - Liu-Ru Fang; Yu-Hua Wang; Zu-Zhao Xiong; Yu-Mei Wang (Elsevier, 2023)
Cancer continues to threaten people's lives and health, and the number of deaths from cancer is very high each year. Traditional treatments such as chemotherapy and surgery are poorly selective and have many side effects. While traditional cancer treatments kill tumor cells, they also damage normal cells and cause a series of toxic side effects. Targeted therapy can compensate for the shortcomings of conventional therapies based on nanomaterials. This paper introduces novel nanomaterials commonly used in tumor-targeted drug delivery as well as imaging therapy, demonstrates the types of active and passive drug delivery systems, and gives examples of research and applications in the past three years. The characteristics of nanomaterials for tumor-targeted therapy and their recent research progress in tumor therapy are summarized. This paper provides theoretical and practical support for nanomaterial-based targeted drug delivery systems and imaging therapy for tumors and provides a reference for the development of nanomaterials for controlled targeted therapy for tumors.